Impact of Parkinson’s Disease- Linked- Lrrk2 Mutation (Lrrk2G2019S) on the Innate Immune Response During Infection with Listeria Monocytogenes. - Sam, Leila (Université d'Ottawa / University of Ottawa, 2020)
Mutations in the Leucine-rich repeat kinase 2 (Lrrk2) gene are associated with familial and sporadic cases of Parkinson’s disease but are also found in inflammatory-related disorders such as Crohn’s disease, systemic lupus erythematosus, tuberculosis and leprosy. There is also evidence that LRRK2 is highly expressed in immune cells, particularly in macrophages, and has been functionally linked to pathways pertinent to immune cell function such as modulating the course of infections, cytokine release, autophagy and phagocytosis. Indeed, G2019S mutation in Lrrk2 is the most common mutation in Parkinson’s disease. Accordingly, we hypothesized that G2019S mutation in Lrrk2 might enhance the activation of the innate immune system. We tested our hypothesis by performing challenge experiments in a mouse model of Listeria monocytogenes, and by measuring the activation of bone marrow derived macrophages (BMDMs) following in vitro infection with the bacterium. We found that Lrrk2G2019S mutant mice controlled L. monocytogenes better than WT mice. The mechanism behind the better control of L. monocytogenes by the G2019S mutation of Lrrk2 was investigated in BMDMs following in vitro infection with L. monocytogenes. Interestingly, we found that Lrrk2G2019S mutation enhances the production of TNF-α, IL-1β and IL-10 by infected BMDMs. The impact on TNF-α and IL-1β was specifically due to the G2019S mutation of Lrrk2 since there was no impact on the expression of these cytokines in Lrrk2 knockout macrophages. Western blotting experiments revealed that the G2019S mutation of Lrrk2 enhances MAPK signaling (TAK1, p38 and ERK). Modulation of the expression of the pro-inflammatory cytokines, TNF-α and IL-1β by G2019S mutation of Lrrk2 occurred via p38 MAPK activation. The impact on IL-10 expression occurred through increased ERK activation by the G2019S mutation of Lrrk2. We did not observe any impact of G2019S mutation of Lrrk2 on the activation of NF-κB and JNK MAPK pathways. Increased expression of IL-1β by G2019S mutation of Lrrk2 revealed increased inflammasome signaling. Inflammasome signaling in response to L. monocytogenes was mainly mediated by the AIM2- and partly by NLRP3- inflammasome and was dependent on activation of caspase-1. We found that Lrrk2G2019S mutation enhanced the expression of NLRP3 and caspase-1. Finally, we found that the expression of reactive oxygen species (ROS) following infection with L. monocytogenes was augmented by G2019S mutation of Lrrk2, and this can be an important mechanism that promotes the enhanced clearance of the bacterium in vivo. Overall, these results present new insights into the signaling mechanisms through which the G2019S mutation of Lrrk2 augments innate immune response which leads to better control of infection.
Keywords: Lrrk2; Listeria monocytogenes; innate immunity